Urgensi Kompetensi Kepribadian Guru Sebagai Upaya Pengembangan Karakter Siswa - Futika Permatasari; Yopi Arianto (IDEA: Jurnal Psikologi, 2022)
Teachers are one of the determinants of educational success and play a major role in achieving educational goals. In addition to the great responsibility of teachers to educate students through the transfer of knowledge, teachers are required to master various kinds of competencies to support the continuity of learning activities. Personality competence is one of the competencies that must be possessed by teachers because as role models for students in learning activities, teachers must present themselves as a teacher profile with a steady and stable personality. The teacher's personality competence is a competence that has a significant influence on the development of student character in accordance with the values ​​and norms that apply in religion and society. Problems related to learning motivation, social behavior, discipline, and student achievement are also influenced by the teacher's personality. Therefore, the teacher's personality competence needs more attention to be developed as an effort to improve the quality of education.